Model of the external force field for the protein folding process—the role of prefoldin - Roterman, Irena; Stapor, Katarzyna; Konieczny, Leszek (Frontiers in Chemistry, 2024)
Introduction: The protein folding process is very sensitive to environmental conditions. Many possibilities in the form of numerous pathways for this process can—if an incorrect one is chosen—lead to the creation of forms described as misfolded. The aqueous environment is the natural one for the protein folding process. Nonetheless, other factors such as the cell membrane and the presence of specific molecules (chaperones) affect this process, ensuring the correct expected structural form to guarantee biological activity. All these factors can be considered components of the external force field for this process. Methods: The fuzzy oil drop-modified (FOD-M) model makes possible the quantitative evaluation of the modification of the external field, treating the aqueous environment as a reference. The FOD-M model (tested on membrane proteins) includes the component modifying the water environment, allowing the assessment of the external force field generated by prefoldin. Results: In this work, prefoldin was treated as the provider of a specific external force field for actin and tubulin. The discussed model can be applied to any folding process simulation, taking into account the changed external conditions. Hence, it can help simulate the in silico protein folding process under defined external conditions determined by the respective external force field. In this work, the structures of prefoldin and protein folded with the participation of prefoldin were analyzed. Discussion: Thus, the role of prefoldin can be treated as a provider of an external field comparable to other environmental factors affecting the protein folding process.